TERRITORIAL AND ETHNIC PECULIARITIES OF DISTRIBUTION OF ACUTE LYMPHOBLASTIC LEUKAEMIA IN CHILDREN'S POPULATION IN KYRGYZSTAN - A.A. USENOVA (Avicenna Tajik State Medical University, 2018)
Objective: Study of territorial and ethnic features of the spread of acute lymphoblastic leukaemia (ALL) in the children of Kyrgyzstan. Methods: The study covers the period from 2006 to 2016 years. All research materials were included, all cases of ALL according to the data of special institutions using statistical methods for processing the received information (SPSS 16.0). Results: During the specified period, 310 cases of ALL were registered in children (age category from 0 to 14 years) in Kyrgyzstan. Most of the high morbidity rates were in Bishkek with an indicator of morbidity 20.80 per 1 million population and Jalal-Abad region with an indicator of 20.08, the lowest values ​​were obtained in Naryn and Batken regions - 15.26 and 11.50, respectively. The incidence of ALL in people of Russian nationality have the highest values, despite a smaller percentage in the quantitative composition (19.77 per 1 million population). Slightly lower - incidence rates among Kyrgyz and Uzbek nationalities, with the values ​​of 19.04 and 18.61 per 1 million of the children's population, respectively. Conclusion: The incidence of ALL in Kyrgyzstan is uneven and has specific features depending on the territory, living conditions (city, village) as well as ethnicity.